On properties of lower k-Hessenberg Toeplitz Matrices - Kirklar, Emrullah,; Yilmaz, Fatih, (Utilitas Mathematica, 2017)
This study investigates lower k-Hessenberg Toeplitz matrices and gives some interesting properties of the matrix family.